Design and development of active learning for large classes - Tan, Jun Xiang (2018)
Designing an active learning approach for a large group of students requires understanding if students would like to learn and interact with professors having a two-way communication compared to conventional lectures where it’s usually unidirectional where little to no interaction takes place during a lecture.